THE ROLE OF COGNITIVE DEVELOPMENT IN ADOLESCENCE: IMPLICATIONS FOR EDUCATION AND MENTAL HEALTH - Rina Farah; Nina Anis; Ruri Angelia Kusuma (Yayasan Adra Karima Hubbi, 2026)
Adolescence is a critical developmental period marked by rapid cognitive, emotional, and social changes that significantly influence learning processes and mental health outcomes. Cognitive development during this stage plays a central role in shaping adolescents’ academic engagement, self-regulation, and psychological well-being, yet it is often examined separately from educational and mental health perspectives. This study aims to investigate the role of cognitive development in adolescence and its implications for both education and mental health within an integrated framework. The research employed a quantitative cross-sectional design involving adolescents aged 13–18 years enrolled in secondary education. Data were collected using standardized instruments measuring cognitive development, educational engagement, and mental health well-being, and were analyzed using descriptive and inferential statistical techniques. The findings reveal significant positive relationships between cognitive development and educational engagement, as well as between cognitive development and mental health indicators. Adolescents with higher levels of cognitive functioning demonstrated stronger academic engagement and better emotional regulation. These results indicate that cognitive development functions as a key mechanism linking learning and mental health during adolescence. The study concludes that educational practices and mental health interventions should prioritize cognitive development as a foundational element.